Chasing a ghost? – Issues with the determination of circulating levels of endotoxin in human blood. (3rd May 2016) - Gnauck, Anne; Lentle, Roger Graham; Kruger, Marlena Cathorina
Abstract: Reliable quantification of bacterial products such as endotoxin is important for the diagnosis of Gram-negative infection and for the monitoring of its treatment. Further, it is important to identify patients with persistent subclinical level of bacterial products in their systemic circulation as data from animal studies also suggest this may be correlated with the onset of metabolic syndrome. In this review, we first aim to describe the principles of the Limulus amoebocyte lysate (LAL) test, an assay that is used to quantify endotoxin, and the various shortcomings that must be addressed before it can become a reliable means of quantifying endotoxin in samples derived from blood. We then review published data regarding endotoxin levels in healthy subjects and those with sepsis, inflammatory bowel disease, liver disorders and metabolic disorders such as obesity and diabetes. We also review the evidence regarding influence of macronutrients in augmenting the levels of systemic endotoxin. The results of this review show that reported mean levels of endotoxin in the systemic circulation of healthy humans and of those with various clinical disorders vary over a wide range. Further, this review shows that a significant proportion of this variation can be related to the method that was used to prepare plasma and serum samples prior to assay and its ability to reduce the effect of various blood borne factors that interfere with the LAL assay.